Začetki slovenskega cecilijanstva v luči korespondence med Antonom Foersterjem in Franzom Xaverjem Wittom - Nagode, Aleš (Muzikološki zbornik, 2007)
Slovenian composer and church musician, Anton Foerster, was until recently considered to be a key figure and ideological leader of the Slovenian Cecilian movement. Newly discovered correspondence between the leader of the German Cecilian movement and editor of the review Musica sacra has cast new light on his role in the Slovenian Cecilian movement. The radical views expressed in his letters differ significantly from the official position of the Cecilian Society. The author of the present article attempts to investigate the consequences of this fact for our understanding of the emergence and development of the Cecilian movement in Slovenia.
Keywords: cecilijanstvo; Foerster, Anton, 1837-1826; katoliška cerkvena glasba; Slovenia; Slovenija